Effectiveness of Implementing Digital Population Identity Applications at the Population and Civil Registration Service of Gorontalo City - Mohamad Zakaria Djafar; Zuchri Abdussamad; Rustam Tohopi (Public Policy Journal, 2025)
This study evaluated the effectiveness of the Digital Population Identity (IKD) application as an effort to improve the quality of public services (speed, efficiency, and transparency) at the Population and Civil Registration Office of Gorontalo City. Using a descriptive qualitative approach with effectiveness parameters covering goal achievement, integration, and adaptation (Duncan), the results showed that the implementation of IKD has not been realized effectively. Indications of ineffectiveness include the level of goal achievement being hindered by low community participation, suboptimal cross-agency integration, and adaptation constraints resulting from limited digital literacy and inadequate technological facilities. Therefore, the study concluded that interventions such as intensified socialization, digital education, and enhanced data security and infrastructure are crucial for optimizing IKD performance.